Feeling Safe and Nostalgia in Healthy Aging - Fleury, Julie; Sedikides, Constantine; Wildschut, Tim; Coon, David W.; Komnenich, Pauline (Frontiers in Psychology, 2022)
The population of older adults worldwide is growing, with an urgent need for approaches that develop and maintain intrinsic capacity consistent with healthy aging. Theory and empirical research converge on feeling safe as central to healthy aging. However, there has been limited attention to resources that cultivate feeling safe to support healthy aging. Nostalgia, “a sentimental longing for one’s past”, is established as a source of comfort in response to social threat, existential threat, and self-threat. Drawing from extant theory and research, we build on these findings to position nostalgia as a regulatory resource that cultivates feeling safe and contributes to intrinsic capacity to support healthy aging. Using a narrative review method, we: (a) characterize feeling safe as a distinct affective dimension to support healthy aging, (b) summarize the character of nostalgia in alignment with feeling safe, (b) propose a theoretical account of the mechanisms through which nostalgia cultivates feeling safe, (c) highlight the contribution of nostalgia to feeling safe and emotional, physiological, and behavioral regulatory capabilities in healthy aging, and (d) offer conclusions and direction for research.